PENGARUH CASH HOLDING, BONUS PLAN, DAN PROFITABILITAS TERHADAP INCOME SMOOTHING DENGAN KUALITAS AUDIT SEBAGAI VARIABEL MODERASI: Indonesia - Oktavinawati Oktavinawati; Vinola Herawaty (Jurnal Ekonomi Trisakti, 2022)
This study aims to examine the effect of cash holding, bonus plan, and profitability on income smoothing with audit quality as a moderating variable..This study uses a sample of manufacturing companies in the basic industry and chemical sectors listed on Indonesia Stock Exchange from 2018 – 2021. The number of manufacturing companies in the basic industry and chemical sectors that were sampled in this study were 28 companies with 4 (four) years of observation. The technique used in data collection is purposive sampling method. The method used in analyzing this research is logistic regression analysis. The results of this study indicate that cash holding has a positive effect on income smoothing. The bonus plan has no positive effect on income smoothing. Profitability does not have a positive effect on income smoothing. Audit quality is able to weaken the effect of cash holding on income smoothing. Audit quality is not able to weaken the effect of the bonus plan on income smoothing. Audit quality is not able to weaken the effect of profitability on income smoothing.